Induction of serine racemase expression and D-serine release from microglia by amyloid β-peptide - Wu, Sheng-Zhou (BioMed Central, 2004)
BACKGROUND: Roles for excitotoxicity and inflammation in Alzheimer's disease have been hypothesized. Proinflammatory stimuli, including amyloid β-peptide (Aβ), elicit a release of glutamate from microglia. We tested the possibility that a coagonist at the NMDA class of glutamate receptors, D-serine, could respond similarly. METHODS: Cultured microglial cells were exposed to Aβ. The culture medium was assayed for levels of D-serine by HPLC and for effects on calcium and survival on primary cultures of rat hippocampal neurons. Microglial cell lysates were examined for the levels of mRNA and protein for serine racemase, the enzyme that forms D-serine from L-serine. The racemase mRNA was also assayed in Alzheimer hippocampus and age-matched controls. A microglial cell line was transfected with a luciferase reporter construct driven by the putative regulatory region of human serine racemase. RESULTS: Conditioned medium from Aβ-treated microglia contained elevated levels of D-serine. Bioassays of hippocampal neurons with the microglia-conditioned medium indicated that Aβ elevated a NMDA receptor agonist that was sensitive to an antagonist of the D-serine/glycine site (5,7-dicholorokynurenic acid; DCKA) and to enzymatic degradation of D-amino acids by D-amino acid oxidase (DAAOx). In the microglia, Aβ elevated steady-state levels of dimeric serine racemase, the apparent active form of the enzyme. Promoter-reporter and mRNA analyses suggest that serine racemase is transcriptionally induced by Aβ. Finally, the levels of serine racemase mRNA were elevated in Alzheimer's disease hippocampus, relative to age-matched controls. CONCLUSIONS: These data suggest that Aβ could contribute to neurodegeneration through stimulating microglia to release cooperative excitatory amino acids, including D-serine.